2021
DOI: 10.22441/oe.2021.v13.i3.035
|View full text |Cite
|
Sign up to set email alerts
|

Performance Management System Design of Inspection Bodies in Indonesia

Abstract: In order to increase economic growth through infrastructure development in Indonesia, the Government has agreed to increase strategic projects that are urgent to be implemented in the short term. The total project investment reaches IDR 4.183 trillion must be controlled and managed properly, this is where the Inspection Body is needed. The number of Inspection Bodies in Indonesia registered with the National Accreditation Committee (KAN) is 169 institutions. Of the total inspection bodies, 120 are active and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Decision-making tools are considered one of the essential elements of robust PMS. The literature review revealed using many decision-making tools to design and construct PMSs, support the decisionmaking process, and select improvement projects as a part of the performance management and improvement process [38], [54], [71], [84], [88]. Therefore, proper decision-making tool/s are mandatory to enhance PMSs' efficiency and effectiveness.…”
Section: Analysis and Interpretationmentioning
confidence: 99%
“…Decision-making tools are considered one of the essential elements of robust PMS. The literature review revealed using many decision-making tools to design and construct PMSs, support the decisionmaking process, and select improvement projects as a part of the performance management and improvement process [38], [54], [71], [84], [88]. Therefore, proper decision-making tool/s are mandatory to enhance PMSs' efficiency and effectiveness.…”
Section: Analysis and Interpretationmentioning
confidence: 99%